Solar treatment (H2O2, TiO2-P25 and GO-TiO2 photocatalysis, photo-Fenton) of organic micropollutants, human pathogen indicators, antibiotic resistant bacteria and related genes in urban wastewater - Nuno F. F. Moreira (2018)
Solar-driven advanced oxidation processes were studied in a pilot-scale photoreactor, as tertiary treatments of effluents from an urban wastewater treatment plant. Solar-H2O2, heterogeneous photocatalysis (with and/or without the addition of H2O2 and employing three different photocatalysts) and the photo-Fenton process were investigated. Chemical (sulfamethoxazole, carbamazepine, and diclofenac) and biological contaminants (faecal contamination indicators, their antibiotic resistant counterparts, 16S rRNA and antibiotic resistance genes), as well as the whole bacterial community, were characterized.& para;& para;Heterogeneous photocatalysis using TiO2-P25 and assisted with H2O2 (P25/H2O2) was the most efficient process on the degradation of the chemical organic micropollutants, attaining levels below the limits of quantification in less than 4 h of treatment (corresponding to Q(UV) <40 kJ L-1). This performance was followed by the same process without H2O2, using TiO2-P25 or a composite material based on graphene oxide and TiO2.& para;& para;Regarding the biological indicators, total faecal coliforms and enterococci and their antibiotic resistant (tetracycline and ciprofloxacin) counterparts were reduced to values close, or beneath, the detection limit (1 CFU 100 mL(-1) ) for all treatments employing H2O2, even upon storage of the treated wastewater for 3-days. Moreover, P25/H2O2 and solar-H2O2 were the most efficient processes in the reduction of the abundance (gene copy number per volume of wastewater) of the analysed genes. However, this reduction was transient for 16S rRNA, int1 and sul1 genes, since after 3-days storage of the treated wastewater their abundance increased to values close to pre-treatment levels. Similar behaviour was observed for the genes qnrS (using TiO2 -P25), blac(CTX-M) and bla(TEM) (using TiO2-P25 and TiO2-P25/H2O2). Interestingly, higher proportions of sequence reads affiliated to the phylum Proteobacteria (Beta- and Gammaproteobacteria) were found after 3-days storage of treated wastewater than before its treatment. Members of the genera Pseudomonas, Rheinheimera and Methylotenera were among those with overgrowth.